15-Hydroxyprostaglandin Dehydrogenase Is a Predictor of Stroke-Associated Pneumonia - Xu, Yunfei; Qiao, Haoduo; Yang, Shun; Zhou, Lin; Zhao, Yao; Xu, Qing; Miao, Shuying; Yuan, Dun; Zhao, Jie; Liu, Ying (Frontiers in Neurology, 2022)
Background and Purpose Stroke is a serious fatal and disabling disease. Stroke-associated pneumonia (SAP) is the most common complication of stroke, which may further aggravate the stroke. The prevention and early prediction of SAP is a key clinical strategy. 15-hydroxyprostaglandin dehydrogenase (15-PGDH) is involved in pneumonia, while its relationship with SAP has yet to be determined. Therefore, we investigated the predictive value of 15-PGDH for SAP and visualized their relationship. Methods Stroke patients were recruited and divided into SAP group and Non-SAP group. Baseline demographic and clinical data were obtained from the medical record system, blood samples were collected to detect relevant variables and 15-PGDH levels. Patient characteristics were compared with a t-test. Binary logistic regression analysis was performed to determine the predictive value of 15-PGDH for SAP. Restricted cubic splines (RCS) were performed to visualize the relationship between 15-PGDH and SAP risk. Finally, the SAP patient characteristics between the severe group and mild group were compared. Results 50 patients were enrolled and divided into SAP group (n = 26) and Non-SAP group (n = 24). 15-PGDH in the SAP group was lower than that in the Non-SAP group (0.258 ± 0.275 vs. 0.784 ± 0.615, p = 0.025). Binary logistic regression analysis revealed that the lower 15-PGDH, the higher the risk of SAP (OR = 0.04, 95%CI, 0.010–0.157, p < 0.001). The RCS model showed the L-shaped relationship between 15-PGDH and SAP. Conclusions In stroke patients, serum 15-PGDH is a valuable biomarker for predicting SAP. There is an L-shaped relationship between the level of 15-PGDH and the risk of SAP.